2018
DOI: 10.3390/s18041173
|View full text |Cite
|
Sign up to set email alerts
|

Optical DNA Biosensor Based on Square-Planar Ethyl Piperidine Substituted Nickel(II) Salphen Complex for Dengue Virus Detection

Abstract: A sensitive and selective optical DNA biosensor was developed for dengue virus detection based on novel square-planar piperidine side chain-functionalized N,N′-bis-4-(hydroxysalicylidene)-phenylenediamine-nickel(II), which was able to intercalate via nucleobase stacking within DNA and be functionalized as an optical DNA hybridization marker. 3-Aminopropyltriethoxysilane (APTS)-modified porous silica nanospheres (PSiNs), was synthesized with a facile mini-emulsion method to act as a high capacity DNA carrier ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Recently, there have been significant developments in highly sensitive molecular point-of-care tests for flaviviruses, such as reverse transcription loop-mediated isothermal amplification (RT-LAMP), reverse transcription recombinase polymerase amplification (RT-RPA), nucleic acid sequence-based amplification (NASBA), transcription-mediated amplification (TMA), helicase-dependent amplification (HDA), and nicking enzyme amplification reaction (NEAR) (Calvert et al, 2017;Ganguli et al, 2017;Kurosaki et al, 2017;Mauk et al, 2017;Priye et al, 2017;Yaren et al, 2018;Castro et al, 2018;Guo et al, 2018;Kim et al, 2018a;Kumar et al, 2018;Lopez-Jimena et al, 2018;Lamb et al, 2018;Sabalza et al, 2018;Song et al, 2018;Zhao and Feng, 2019;Abd et al, 2017;Chan et al, 2018;Tan et al, 2018;Vasileva Wand et al, 2018;Saa et al, 2018). Microfluidics, chips, paper-based devices, and biosensors are also being developed (Onyango et al, 2017;Adegoke et al, 2017;Afsahi et al, 2018;Ariffin et al, 2018;Wasik et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been significant developments in highly sensitive molecular point-of-care tests for flaviviruses, such as reverse transcription loop-mediated isothermal amplification (RT-LAMP), reverse transcription recombinase polymerase amplification (RT-RPA), nucleic acid sequence-based amplification (NASBA), transcription-mediated amplification (TMA), helicase-dependent amplification (HDA), and nicking enzyme amplification reaction (NEAR) (Calvert et al, 2017;Ganguli et al, 2017;Kurosaki et al, 2017;Mauk et al, 2017;Priye et al, 2017;Yaren et al, 2018;Castro et al, 2018;Guo et al, 2018;Kim et al, 2018a;Kumar et al, 2018;Lopez-Jimena et al, 2018;Lamb et al, 2018;Sabalza et al, 2018;Song et al, 2018;Zhao and Feng, 2019;Abd et al, 2017;Chan et al, 2018;Tan et al, 2018;Vasileva Wand et al, 2018;Saa et al, 2018). Microfluidics, chips, paper-based devices, and biosensors are also being developed (Onyango et al, 2017;Adegoke et al, 2017;Afsahi et al, 2018;Ariffin et al, 2018;Wasik et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The fiber optic reflectance spectrophotometer was used to measure the reflectance intensity of hybridization of target DNA with probe DNA. The study demonstrated that genosensor was capable to detect dengue DNA with a LOD of 0.2 aM [35].…”
Section: Detection Of Dengue Genomementioning
confidence: 93%
“…Biosensors utilize different mechanisms namely, electrochemical, optical or piezoelectric transduction and surface plasmon resonance (SPR) to detect viral pathogens [98][99][100]. Application of biosensors to detect dengue virus has been reported in several studies [101][102][103][104][105]. In those studies, a range of biosensor-based diagnostic technologies like surface plasmon resonance (SPR) to detect dengue viruses in the serum, saliva and urine samples using different biomarkers complementary DNA (cDNA), IgM antibody and non-structural protein 1 (NS1) antigen was demonstrated with the promising limit of detections as shown in Table 3.…”
Section: Emerging Diagnostic Technologies For Dengue Virus Infectionmentioning
confidence: 99%